2006
DOI: 10.1128/cvi.00037-06
|View full text |Cite
|
Sign up to set email alerts
|

Human Neutralizing Fab Molecules against Severe Acute Respiratory Syndrome Coronavirus Generated by Phage Display

Abstract: Human recombinant Fab fragments specific for the spike protein of severe acute respiratory syndrome coronavirus (SARS-CoV) were screened from a human Fab library, which was generated from RNAs from peripheral lymphocytes of convalescent SARS patients. Among 50 randomly picked clones, 12 Fabs specially reacted with S protein by an enzyme-linked immunosorbent assay. The microneutralizing test showed that one clone, designated M1A, had neutralizing activity on Vero E6 cells against SARS-CoV. DNA sequence analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…Thus, T4 Hoc and Soc displaying short, random peptide sequences have been used to discover additional phage proteins that bind the terminase protein, gp17, via selection method called biopanning that uses multiple rounds of screening to find molecules that bind with high affinity to chosen target ( Figure 4 D) [ 126 ]. Other applications include screening vaccine candidates, drug discovery, or as biosensors to detect specific antigens [ 127 , 128 , 129 , 130 , 131 , 132 ].…”
Section: Nanotechnology Applicationsmentioning
confidence: 99%
“…Thus, T4 Hoc and Soc displaying short, random peptide sequences have been used to discover additional phage proteins that bind the terminase protein, gp17, via selection method called biopanning that uses multiple rounds of screening to find molecules that bind with high affinity to chosen target ( Figure 4 D) [ 126 ]. Other applications include screening vaccine candidates, drug discovery, or as biosensors to detect specific antigens [ 127 , 128 , 129 , 130 , 131 , 132 ].…”
Section: Nanotechnology Applicationsmentioning
confidence: 99%
“…One example is the identification of an scFv antibody, called B1, which binds the S2 of the spike protein of the SARS-CoV both in vitro and in vivo, exhibiting a potent neutralizing activity [ 94 ]. Moreover, this same technique allowed for the detection of a human Fab (Fragment antigen-binding) molecule against the spike protein of SARS-CoV, named M1A that could be used in passive immunoprophylaxis [ 95 ]. However, the Fc (Fragment crystallizable) region of the antibody is needed to enable the development of a proper immune response [ 96 ], so structural modifications (as the authors suggested) would be interesting in order to enhance its protective and neutralizing capacities.…”
Section: Bacteriophagesmentioning
confidence: 99%
“…Other antibodies were selected from immune antibody gene libraries targeting e.g. WEEV [48], HIV [80,122], SARS [59], Yellow fever virus [27] or Influenza virus [116,119]. Even semi-synthetic libraries were used to generate antibodies specific for Influenza virus [9].…”
Section: Recombinant Antibodies Against Virusesmentioning
confidence: 99%